POTRET SOSIAL MASYARAKAT URBAN DI KOTA METROPOLITAN DALAM NOVEL JALA KARYA TITIS BASINO: KAJIAN SOSIOLOGI SASTRA - Inung Setyami (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2021)
This study aims to describe the social portrait of urban society in a metropolitan city in the novel Jala by Titis Basino studied using the sociological theory of literature. The data source of this research is the novel Jala by Titis Basino, published in 2002 by Bentang Publisher, Yogyakarta. This research is a qualitative descriptive study. The results show Jala represents a portrait of urban life in the metropolitan city of Jakarta. Basically, this novel indirectly presents a criticism of social problems that occur, including 1) social problems in the political and economic fields. 2) These problems are divided into several variants of phenomena, namely the problem of the rulers' policies that oppress the little people, the eviction and closure of informal businesses of the little people, and the problem of poverty.